Bilateral cricoarytenoid joint involvement in rheumatoid arthritis: a case report - Kamanli, A; Gok, U; Sahin, S; Kaygusuz, I; Ardicoglu, O; Yalcin, S (Oxford Univ Press, 2001)
[Abstract Not Available]